2021
DOI: 10.1038/s41598-020-80364-4
|View full text |Cite|
|
Sign up to set email alerts
|

Deficit saline water irrigation under reduced tillage and residue mulch improves soil health in sorghum-wheat cropping system in semi-arid region

Abstract: Judicious application of saline water except for critical growth stages, could be the only practical solution to meet the crop water demand in arid and semi-arid regions, due to limited access to freshwater, especially during dry winter months. A field experiment was conducted to study the effect of tillage [conventional (CT), reduced (RT), and zero (ZT)], rice straw mulch and deficit saline-water irrigation in wheat (100, 80 and 60% of wheat water requirement, CWR) followed by rainfed sorghum on soil properti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…Soil biodiversity and soil health can be greatly improved by the management of fungal and bacterial communities [7], disruption of pathogenic organisms [8], adding more organic matter to the soil [9], reducing tillage frequency and intensity [10], crop rotation, and adopting sustainable farming practices [11]. Results of various scientific studies have shown that conventional and organic farming systems greatly affect soil biodiversity and all production parameters.…”
Section: Soil Life and Soil Healthmentioning
confidence: 99%
“…Soil biodiversity and soil health can be greatly improved by the management of fungal and bacterial communities [7], disruption of pathogenic organisms [8], adding more organic matter to the soil [9], reducing tillage frequency and intensity [10], crop rotation, and adopting sustainable farming practices [11]. Results of various scientific studies have shown that conventional and organic farming systems greatly affect soil biodiversity and all production parameters.…”
Section: Soil Life and Soil Healthmentioning
confidence: 99%
“…Sub-tropical northern Indo-Gangetic Plains (Masto et al 2007) Maize-wheat KMnO 4 oxidizable N, SOC, MBC, alkaline phosphatase activity, bulk density and DTPA Zn Sub-tropical lower Indo-Gangetic Plains (Chaudhury et al 2005) Jute-rice-wheat Olsen's P and NH 4 OAc extractable K, MBC, mean weight diameter and SOC Brahmaputra Valley (Mandal et al 2005) Rice-rice NH 4 OAc extractable K, DTPA Zn, SOC, per cent base saturation and dehydrogenase activity East and south-eastern coastal plain (Majhi et al 2019) Rice-rice Cation exchange capacity, reserve K, total N and DTPA Zn Sub-tropical northern Indo-Gangetic Plains (Purakayastha et al 2019) Rice-wheat Wheat-vegetables SOC, DTPA Zn, and Mn, NH 4 OAc extractable K, aggregate stability, MBC and mineralizable N Sub-tropical northern saline soil of Indo-Gangetic Plains (Soni et al 2021) Sorghum-wheat α-glucosidase activity, MBC, electrical conductivity (EC e ), KMnO 4 oxidizable N, MBC:MBN after sorghum and MBC:MBN, EC e , MBC, urease activity, KMnO 4 oxidizable N after wheat to soil living system (Lohan et al 2018). Rehabilitating and reverting from degradation or regaining its productive state needs time and expensive corrective measures (Mandal et al 2016;Basak et al 2014).…”
Section: Hydraulic Conductivity Clay and Alkalinitymentioning
confidence: 99%
“…Minimizing the disturbances through adoption of reduced (no) tillage practices, logically facilitate the hoarding of C into soil and accordingly the problem of global climate change can be reduced and soil quality be improved. The reduced tillage practice is beneficial upon conventional tillage with known benefit of SOC hoarding in the surface soil due to congenial soil temperature and moisture regime and protection of top soil erosion (Soni et al 2021). The positive effect of reduced tillage is likely to be greater in tropical and subtropical than the temperate regions.…”
Section: Organic C and Soil Qualitymentioning
confidence: 99%
“…On the 6 th field of the 1 st and 3 rd crop rotation schemes, melilot is used as a cover crop, and on the 6 th field of the 2 nd scheme, DCs are sown. Because sorghum is a moderately salt-tolerant crop (Soni et al 2021), after harvesting the DCs, it is possible successfully cultivate sorghum or millet as a second crop and green fodder. We suggest that this approach can contribute to a rational and effective use of lands because less irrigation will reduce secondary salinization at the same time saving water, while inclusion of DCs will facilitate maintaining soil health (Soni et al 2021).…”
Section: Crop Rotations Schemesmentioning
confidence: 99%